TrkB signalling pathway mediates the protective effects of exercise in the diabetic rat retina. (3rd April 2018) - Allen, Rachael S.; Hanif, Adam M.; Gogniat, Marissa A.; Prall, Brian C.; Haider, Raza; Aung, Moe H.; Prunty, Megan C.; Mees, Lukas M.; Coulter, Monica M.; Motz, Cara T.; Boatright, Jeffrey H.; Pardue, Machelle T.
Abstract: Diabetic retinopathy is a leading cause of vision loss. Treatment options for early retinopathy are sparse. Exercise protects dying photoreceptors in models of retinal degeneration, thereby preserving vision. We tested the protective effects of exercise on retinal and cognitive deficits in a type 1 diabetes model and determined whether the TrkB pathway mediates this effect. Hyperglycaemia was induced in Long Evans rats via streptozotocin injection (STZ; 100 mg/kg). Following confirmed hyperglycaemia, both control and diabetic rats underwent treadmill exercise for 30 min, 5 days/week at 0 m/min (inactive groups) or 15 m/min (active groups) for 8 weeks. A TrkB receptor antagonist (ANA‐12), or vehicle, was injected 2.5 h before exercise training. We measured spatial frequency and contrast sensitivity using optokinetic tracking biweekly post‐STZ; retinal function using electroretinography at 4 and 8 weeks; and cognitive function and exploratory behaviour using Y‐maze at 8 weeks. Retinal neurotrophin‐4 was measured using ELISA. Compared with non‐diabetic controls, diabetic rats showed significantly reduced spatial frequency and contrast sensitivity, delayed electroretinogram oscillatory potential and flicker implicit times and reduced cognitive function and exploratory behaviour. Exercise interventions significantly delayed the appearance of all deficits, except for exploratory behaviour. Treatment with ANA‐12 significantly reduced this protection, suggesting a TrkB‐mediated mechanism. Despite this, no changes in retinal neurotrohin‐4 were observed with diabetes or exercise. Exercise protected against early visual and cognitive dysfunction in diabetic rats, suggesting that exercise interventions started after hyperglycaemia diagnosis may be a beneficial treatment. The translational potential is high, given that exercise treatment is non‐invasive, patient controlled and inexpensive. Abstract : STZ‐induced diabetic rats undergoing treadmill exercise show reduced visual and retinal dysfunction in early‐stage disease. Cognitive dysfunction occurred after detection of retinal deficits, but still benefited from the exercise intervention. Treatment with the TrkB antagonist, ANA‐12, blocked the protective effects of exercise on retinal and cognitive dysfunction, suggesting that exercise activates a TrkB pathway signalling mechanism.